Terapi Buerger Allen Exercise untuk Perbaikan Sirkulasi Darah Perifer pada Pasien Diabetes Mellitus Tipe 2 - Yammar, Yammar; Wardanengsih, Ery; Utami, Dian Fahmi; Barangkau, Barangkau; Darwis, Nirmawati; Fatmawati, Fatmawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Type 2 diabetes mellitus is a disorder of the body's metabolism which is characterized by increased blood glucose levels for a long time, resulting in neuropathy and vascular complications. Type 2 diabetes mellitus with peripheral circulation disorders has become a global health problem with the incidence rate continuing to increase every year. Because non-pharmacological treatment is needed, one of which is the provision of Buerger Allen exercise therapy. The aim of this study was to determine the effect of Buerger Allen exercise therapy on improving peripheral blood circulation in patients with type 2 diabetes mellitus. This study was a literature review. Information was obtained from two databases, namely Google Scholar and PubMed with publications in national and international journals from 2019 to 2023. Articles were selected based on abstract and full text so that six articles were obtained with details of two articles from PubMed and four articles from Google Scholar. Of the six articles, all articles showed a p value of less than 0.05 for the analysis of the effect of Buerger Allen exercises therapy with a p value <0.05. It can be concluded that Buerger Allen exercise therapy has been proven to improve peripheral circulation in patients with type 2 diabetes mellitus.Keywords: diabetes mellitus; burger allen exercise; peripheral circulation ABSTRAK Diabetes mellitus tipe 2 merupakan gangguan pada metabolisme tubuh yang ditandai dengan meningkatnya kadar glukosa darah dalam waktu yang lama, sehingga muncul komplikasi neuropati dan komplikasi vaskuler. Diabetes mellitus tipe 2 dengan gangguan sirkulasi perifer telah menjadi masalah kesehatan global dengan angka kejadian terus meningkat setiap tahun. Oleh karena perlu penanganan non farmakologis, salah satunnya adalah pemberian terapi buerger allen exercise. Tujuan dari studi ini adalah untuk mengatahui pengaruh terapi buerger allen exercise terhadap perbaikan sirkulasi darah perifer pada pasien diabetes mellitus tipe 2. Studi ini merupakan literature review. Informasi diperoleh dari dua database yaitu Google Scholar dan PubMed dengan publikasi jurnal-jurnal nasional dan internasional dari tahun 2019 hingga 2023. Artikel dipilih berdasarkan abstrak dan fulltext sehingga diperoleh enam artikel dengan rincian dua artikel dari PubMed dan empat artikel dari Google Scholar. Dari keenam artikel tersebut, semua artikel menunjukkan nilai p kurang dari 0,05 untuk analisis pengaruh terapi buerger allen exercises terhadap dengan nilai p <0,05. Dapat disimpulkan bahwa terapi buerger allen exercise terbukti dapat memperbaiki sirkulasi perifer pada pasien diabetes mellitus tipe 2.Kata kunci: diabetes mellitus; buerger allen exercise; sirkulasi perifer